A point mutation in the VP4 coding sequence of coxsackievirus B4 influences virulence. - Ramsingh, A I (1995)
In analyzing the molecular determinants of virulence of coxsackievirus B4, chimeric viruses were constructed from avirulent and virulent viruses. The vCB424 recombinant contained a single nucleotide substitution on an avirulent genetic background, resulting in replacement of Ser-16 of VP4 with Arg-16. Mice infected with vCB424 displayed an intermediate phenotype.